CIPP Evaluation of the Archery Achievement Development Program for Surakarta Special Sports Middle Schools in 2024 (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to evaluate the archery achievement development program implemented at the Special Sports Junior High School in Surakarta in 2024. Using a qualitative evaluative approach and a case study design, the research applies the context, input, process, and product evaluation model to analyze all dimensions of the program comprehensively. Data were collected through document analysis, structured questionnaires, and interviews with key stakeholders, including program managers, coaches, and athletes. Narrative descriptive analysis was employed to organize and interpret the data according to each evaluation component. The findings show that the program's objectives are highly aligned with national sports development goals and are supported by a strong vision shared among stakeholders. The input evaluation revealed excellent human resources and a rigorous athlete selection process, although significantly hindered by inadequate training facilities. The process component demonstrated well-structured and science-based training methods, including psychological preparation. In terms of outcomes, the program succeeded in producing high-performing athletes who achieved success at the national level. However, the lack of permanent training infrastructure presents a critical challenge to the program’s sustainability. The study concludes that while the program is effective in achieving its short-term goals, long-term improvements must prioritise the provision of dedicated training facilities to support continued athlete development.